Effectiveness and Drug Survival of Anti-Tumor Necrosis Factor Therapies in Patients with Spondyloarthritis: Analysis from the Thai Rheumatic Disease Prior Authorization Registry - Praveena Chiowchanwisawakit (2019)
© 2018 Wolters Kluwer Health, Inc. All rights reserved. Objective This study aimed to evaluate the long-term effectiveness and safety of the first anti-tumor necrosis factor therapy (TNFi) and to identify the associated factors of drug discontinuation in patients with spondyloarthritis. Methods This was a medical records review study. Patients with spondyloarthritis who were prescribed the first TNFi between December 2009 and October 2014 in the Rheumatic Disease Prior Authorization registry were enrolled. Baseline clinical data were retrieved. The Cox proportional hazards model was used to identify factors associated with discontinuation of drugs. Results Among 138 patients, 97 had ankylosing spondylitis (AS), and 41 had psoriatic arthritis (PsA). The effectiveness of TNFi in AS and PsA was 55% to 59% at 4 months and 75% to 96% at 3 years, as measured by a 50% decrease in the Bath Ankylosing Spondylitis Disease Activity Index from baseline. For PsA with peripheral arthritis, improvement of the joint count by 50% was observed in 61.8% of patients at 4 months and 100% at 3 years. Survival from TNFi was 63% for AS and 56% for PsA at 3 years. For AS, the factors associated with good response leading to discontinuation of TNFi were baseline patient global assessment 3 to 6/10 (hazard ratio [HR], 6.3) and the use of leflunomide (HR, 6.0) and infliximab (HR, 4.8). A good response (38.5%) was the most common cause of discontinuation of the first TNFi, followed by toxicity (28.2%), nonadherence (20.5%), and lack of effectiveness (12.8%). Conclusions Ankylosing spondylitis and PsA responded well to TNFi during the 3-year follow-up. The retention rate was approximately 60% for AS and PsA. A good response to the first TNFi was the most common reason for discontinuation.